PENGARUH MOTIVASI TERHADAP KOMITMEN ORGANISASIONAL DENGAN KEPUASAN KERJA SEBAGAI PEMEDIASI (Survei pada Karyawan Kantor Pelayanan Perbendaharaan Negara/KPPN Area Surakarta) - Rahayu Triastity, Edy Suwignyo, Amin Wahyudi & (Universitas Slamet Riyadi, 2017)
This research aims to analyses the role of job satisfaction as mediatingvariable of the effect intrinsic motivation and extrinsic motivation onorganizational commitment. This study is sensus research, using location inState Treasury Service Office/KPPN Surakarta areas,, using sample of 109employees. To test hypothesis using path analysis. The result shows that (1)intrinsic motivation has significance effect on job satisfaction, so thehypothesis 1 accepted; (2)extrinsic motivation has significance effect on jobsatisfaction, so the hypothesis 2 accepted; (3) ) intrinsic motivation hassignificance effect on organizational commitment, so the hypothesis 3accepted; (4) extrinsic motivation has significance effect on organizationalcommitment, so the hypothesis 4 accepted; (5) has significance effect on jobsatisfaction, so the hypothesis 5 accepted; (6) effect of intrinsic motivation onorganizational commitment mediated job satisfaction, so the hypothesis 6accepted; (7) effect of extrinsic motivation on organizational commitmentmediated job satisfaction, so the hypothesis 7 accepted.Keywords: intrinsic motivation, extrinsic motivation, job satisfaction,organizational commitment